2015
DOI: 10.1017/s1068280500010212
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn about Shale Gas Development from Land Values? Opportunities, Challenges, and Evidence from Texas and Pennsylvania

Abstract: We study farm real estate values in the Barnett shale (Texas) and the northeastern part of the Marcellus shale (Pennsylvania and New York). We find that shale gas development caused appreciation in real estate values in both areas but the effect was much larger for the Marcellus, suggesting broader ownership of oil and gas rights by surface owners. In both regions, the greatest appreciation occurred when land was leased for drilling, not when drilling and production boomed. We find evidence that effects vary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
2
15
1
Order By: Relevance
“…Since only 28 percent of the housing transactions in their study involved an active lease, leasing would account for an average increase in housing values of just 1 percent. This is consistent with Weber and Hitaj (), who find evidence from farm real estate values in the Barnett Shale that surface owners generally do not own the rights to the gas beneath the surface.…”
Section: Alternative Interpretations and Confounding Factorssupporting
confidence: 90%
“…Since only 28 percent of the housing transactions in their study involved an active lease, leasing would account for an average increase in housing values of just 1 percent. This is consistent with Weber and Hitaj (), who find evidence from farm real estate values in the Barnett Shale that surface owners generally do not own the rights to the gas beneath the surface.…”
Section: Alternative Interpretations and Confounding Factorssupporting
confidence: 90%
“…Land price has also an informational content about underground resources not directly related to the agricultural use. Recent papers have called for attention to be paid to the presence of shale gas development opportunities which might affect the findings obtained from hedonic regressions on land prices, due to dis-amenities caused by such natural opportunities (Weber and Hitaj, 2015). Among the extrinsic attributes capitalized in land prices, institutions and human improvements are also investigated though the PVM applied to land prices.…”
Section: The Value Of Intrinsic Environmentmentioning
confidence: 99%
“…In both zones, most appreciation of farmlands occurred exactly when land was leased for drilling, not when drilling and production were at their peak. They found that the effects changed by agricultural land type, which may mirror a connection between agricultural land types and the presence of mineral rights, in here, the ownership of oil and gas rights (Weber and Hitaj, 2015).…”
Section: Agricultural Land Valuesmentioning
confidence: 77%
“…In addition, the study conducted by (Baen, 1996) found oil and gas activities cause damage to surface land, therefore, the surface land loses its property value. Also, (Weber and Hitaj, 2015) mentioned in the conclusion of his study the two mechanisms of mineral rights when he concluded that drilling can create ecological disamenities and influence the land's suitability for the utilizations that give it value and that Shale gas development influences self-reported agricultural real estate values. Some farmers incorporate their oil and gas rights in the market estimation of their property.…”
Section: Comparing Our Study Results To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation